2022
DOI: 10.1021/acs.energyfuels.2c02751
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of CO2 Soaking and Flooding Processes in Tight Oil Reservoirs

Abstract: CO 2 injection has been proven to be an effective method to improve oil recovery of tight oil reservoirs. CO 2 soaking and flooding are common processes used to constitute some CO 2 injection patterns. To investigate the difference of oil recovery performance and asphaltene precipitation distribution between CO 2 soaking and CO 2 flooding processes, CO 2 soaking and flooding tests under immiscible and miscible conditions were carried out with tight core samples. Then the NMR technique was utilized to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, Zhu et al found that residual oil is concentrated in clay micropores. Qian et al pointed out that huff and puff extraction is more effective than displacement methods in preventing asphaltene deposition in reservoirs. Huang et al investigated the deposition characteristics of asphaltenes and reservoir damage during the huff and puff process through NMR, noting that the precipitation rate of asphaltenes decreases with increasing huff and puff rounds.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zhu et al found that residual oil is concentrated in clay micropores. Qian et al pointed out that huff and puff extraction is more effective than displacement methods in preventing asphaltene deposition in reservoirs. Huang et al investigated the deposition characteristics of asphaltenes and reservoir damage during the huff and puff process through NMR, noting that the precipitation rate of asphaltenes decreases with increasing huff and puff rounds.…”
Section: Introductionmentioning
confidence: 99%